Implementasi Alat Penyiraman Tanaman Otomatis Berbasis Internet Of Things Menggunakan Metode Fuzzy Logic Pada Kebun Artawi Flora - Gilang Fauzi; Maulana Ardhiansyah (STIE AUB Surakarta, 2022)
Artawi Flora is an ornamental plant cultivation entrepreneur since 2009 located in the city of Bogor, precisely on Jl. Mutiara 4 RT 003RW 002 Number 21 Desa Curug, Kecamatan Gunung Sindur. In Artawi Flora gardens, they still do not take advantage of technological developments, so there is no tool for monitoring soil moisture that can automatically water plants and monitor temperature on plantations, the watering process is carried out manually which causes excess or lack of water so that it has the potential to die in plants, by watering Planting manually requires extra labor which causes it to be less efficient. The purpose of this research is to make an internet of things-based automatic plant watering tool. It is hoped that the presence of an automatic plant watering device can make it easier to water plants. This study uses the fuzzy logic method as a method for the control system, the fuzzy logic method has several stages, namely fuzzyfication, inference, and defuzzification. The development method used in this research is the prototype method. And the system testing method used is the black box method. Based on the implementation and testing of the system, it can be said that this internet of things-based automatic plant watering tool can help make it easier for farmers to water plants and monitor temperature in plantations.